The impact of aerobic exercise on overall health, chronic disease management and COVID-19 outcomes – a literature review - Koziński, Tomasz; Donderska, Marta; Kwiatkowski, Marcin; Bochniak, Paulina; Kołacz, Jakub; Oleś, Patrycja; Bryła, Mateusz; Bryła, Zofia; Spaczyńska-Kwiatkowska, Monika; Włoch, Tomasz (Journal of Education, Health and Sport, 2025)
Introduction and purpose Physical activity and aerobic exercise have long been recognized as foundational to maintaining good health. Insufficient activity is linked to be a factor contributing to many chronic diseases, as well as a worse prognosis for COVID-19 infection. This review aims to present the current state of knowledge regarding aerobic exercise and physical activity – and to present this information to doctors and other medical staff, as well as to those who seek help in our healthcare system. State of knowledge Currently, there is a common understanding that, without physical activity, the human body begins to experience physiological changes. This is manifested in deteriorating health and a greater risk of falling into disorders such as cardiovascular disease, mental health problems, and metabolic syndrome. With the outbreak of the COVID-19 pandemic, it was also understood that individuals with a worse state of overall health (with many risk factors) have a greater risk of severe cases of this infection and more serious complications. Conclusions Despite all the knowledge, there is still room to improve our understanding of this topic, creating clearer guidelines, and educating healthcare professionals and patients on the importance of physical activity. Therefore, it is important to investigate further the root causes and mechanisms behind both the positive effects of increasing physical activity and the negative effects of inactivity.